Stress escapism, solo traveler motivation in terms of consumer behavior - Nuri Purwanto; Langgeng Prayitno Utomo; Kristin Juwita (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
This study aims to find and analyze the motivation of millenials generation to do solo traveling. The method used in this research is qualitative with a case study approach. The data analysis was Miles and Huberman’s model and tested by triangulation of sources. The result of this study found several motivations for millenials generation doing solo traveling, including consumer behavior that indicates psychological factors, utilitarian motivation, and hedonic motivation. This study also found that the dominant factor is hedonic motivation, which satisfies the emotional aspect.